Abrasive blasting of lithium metal surfaces yields clean and 3D structured lithium metal anodes with superior properties - Wolf, Andreas; Lorrmann, Henning; Flegler, Andreas; Wolf, Andreas J.; Guerﬁ, Abdelbast; Mandel, Karl; Giffin, Guinevere A. (Energy Technology, 2021)
Avoiding harmful passivation of the lithium metal surface during its implementation as an anode material is a challenge to its use in rechargeable lithium metal batteries. It is critical to control the chemical composition and the morphology of the native passivation layer and to avoid contamination by lubricants or other substances involved in the processing. Herein, abrasive blasting is used as a physical method to achieve clean and 3D-structured lithium metal electrodes. The careful choice of the abrasive agent and the blasting parameters results in well-controlled surface properties. The blasted lithium electrodes exhibit significantly lower overvoltages with values as low as 10 mV at 0.1 mA cm−2. Electrochemical impedance spectroscopy shows that blasted lithium has interface resistances that are up to five times smaller than those of untreated lithium. The effectiveness of blasting as a cleaning method is clear even in the case of thicker and highly resistive passivation layers occurring after exposure to ambient air.

A Roadmap for Transforming Research to Invent the Batteries of the Future Designed within the European Large Scale Research Initiative BATTERY 2030+ - Amici, Julia; Asinari, Pietro; Ayerbe, Elixabete; Barboux, Philippe; Bayle-Guillemaud, Pascale; Behm, R. Juergen; Berecibar, Maitane; Berg, Erik; Bhowmik, Arghya; Bodoardo, Silvia; Castelli, Ivano E.; Cekic-Laskovic, Isidora; et al. (Advanced Energy Materials, 2022)
This roadmap presents the transformational research ideas proposed by "BATTERY 2030+," the European large-scale research initiative for future battery chemistries. A "chemistry-neutral" roadmap to advance battery research, particularly at low technology readiness levels, is outlined, with a time horizon of more than ten years. The roadmap is centered around six themes: 1) accelerated materials discovery platform, 2) battery interface genome, with the integration of smart functionalities such as 3) sensing and 4) self-healing processes. Beyond chemistry related aspects also include crosscutting research regarding 5) manufacturability and 6) recyclability. This roadmap should be seen as an enabling complement to the global battery roadmaps which focus on expected ultrahigh battery performance, especially for the future of transport. Batteries are used in many applications and are considered to be one technology necessary to reach the climate goals. Currently the market is dominated by lithium-ion batteries, which perform well, but despite new generations coming in the near future, they will soon approach their performance limits. Without major breakthroughs, battery performance and production requirements will not be sufficient to enable the building of a climate-neutral society. Through this "chemistry neutral" approach a generic toolbox transforming the way batteries are developed, designed and manufactured, will be created.
CRIS-Team WoS Importer:2022-01-28
Keywords: battery 2030+ roadmap; battery interface genome; chemistry neutral approach; manufacturing; materials acceleration platform; recycling; smart battery functionalities

Bulk Magnetic Properties Arise from Micron‐Sized Supraparticle Interactions and Can be Modified on the Nanoscale - Wolf, Andreas; Heinlein, Markus; Kent, Noah; Müssig, Stephan; Mandel, Karl (Small, 2025)
Magnetic supraparticles (SPs) can be employed as micron-sized particulate additives in arbitrary objects to serve as ID-tag or recorder of environmental triggers. Combined with magnetic particle spectroscopy (MPS), which enables read-out of the magnetic information in ambient conditions within seconds, magnetic SPs represent a powerful approach to equip materials with information. The encoded information relies on magnetic interactions within the SPs (intra-SP interactions) of chosen nanoparticles (NPs). However, possible magnetic interactions between SPs (inter-SP interactions), that might alter the MPS signal as well, have been neglected so far. Herein, it is elucidated that significant inter-SP interactions exist and that they can be tailored via adjustments in the SP structure, i.e., by defined adjustments of their intra-interaction as revealed by 3D-MuMax simulations and experiments in viscous fluids. Superparamagnetic iron oxide nanoparticle-based SP powders with strong inter-SP interactions exhibit significantly different MPS signals compared to their state after being incorporated into a matrix. Powders with weak inter-SP interactions (achieved by integration of non-magnetic SiO2 nanoparticles) show almost no signal change before and after incorporation. Both extremes of inter-SP interactions can be beneficial for various application scenarios and can be tailored on the nano-scale due to the interdependency of intra- and inter-SP interaction
CRIS-Team Scopus Importer:2025-03-07
Keywords: magnetic interactions; magnetic particle spectroscopy; matrix interactions; supraparticles

Centrifugation based separation of lithium iron phosphate (LFP) and carbon black for lithium-ion battery recycling - Wolf, Andreas; Flegler, Andreas; Prieschl, Johannes; Stuebinger, Thomas; Witt, Wolfgang; Seiser, Felix; Vinnay, Thomas; Sinn, Tabea; Gleiß, Marco; Nirschl, Herrmann; Mandel, Karl (Chemical Engineering and Processing, 2021)
Semi-continuous centrifugation is suggested as promising method to separate battery active materials from aqueous multi-component agglomerate dispersions. This is of special interest for direct recycling of active materials from decommissioned lithium-ion batteries. The separation of lithium iron phosphate (LFP) from carbon black C65 could be achieved with separation efficiencies of 90–100 % for LFP and 40–90 % for C65. The working parameters of the centrifuge, namely volumetric flow rate and rotational speed, were varied within a design of experiments study to find an optimum at 65 mL min−1 and 20,000 rpm, where at least 97 % of the LFP is separated in the centrifuge, while as much C65 as possible is pushed into the centrate. Furthermore, the separation mechanism was discussed by analyzing particle size distributions and the sediment build-up. High rotational speeds and low volumetric flow rates lead to significant radial and axial gradients in terms of carbon content in the sediment. LFP that was extracted from the sediment after centrifugation at the optimum conditions exhibited 98 % of the initial specific capacity.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Battery recycling; Centrifuge; Design of experiments; Lithium iron phosphate; Particle separation; Particle size analysis

Circular battery design: investing in sustainability and profitability - Wolf, Andreas; Nagler, Felix; Daubinger, Philip; Neef, Christoph; Mandel, Karl; Flegler, Andreas; Giffin, Guinevere A. (Energy and Environmental Science, 2024)
Sustainability along the battery value chain is a much talked about goal but currently comes third after cost and performance. Historically, improved sustainability comes with a penalty in terms of cost and performance. This interplay will certainly evolve in the coming years. Ecological and social aspects driven by legislative frameworks guarantee recycling of lithium-ion batteries (LIBs) to prevent hazardous waste in landfills. The trend in the electric vehicle (EV) sector towards low-cost chemistries like lithium iron phosphate (LFP) represents a double-edged sword, as the recycling profitability of such materials is extremely low for the established recycling methods. Extending battery lifetime and enabling direct recycling, where anode and cathode materials maintain their structure and functionality, are key strategies to increase sustainability and profitability. However, their implementation necessitates a shift in LIB design priorities. This Perspective highlights design for circularity as an enabler for improved battery longevity and direct recycling and represents a key tipping element for reducing cost and increasing sustainability in LIB production and disposition concurrently. We outline challenges and opportunities in battery production with special focus on the European EV sector and define actions required from various stakeholders along the value chain to overcome the mindset of linear economies.
CRIS-Team Scopus Importer:2024-10-25

Influence of magnetic interactions in iron oxide nanoparticle polymer composites on magnetism and induction heating - Raczka, Theodor; Wolf, Andreas; Reichstein, Jakob; Stauch, Claudia; Schug, Benedikt; Müssig, Stephan; Mandel, Karl (Journal of Magnetism and Magnetic Materials, 2024)
Induction heating of composite materials is of great interest in fields such as controlled polymer curing or degradation, self-healing or contactless joining. Ferrimagnetic iron oxide nanoparticle (IONPs) are suitable candidates for a powder additive to provide this inductive heating functionality, while being low-cost, abundant and a well-studied material class. Varying IONP size, morphology or doping facilitates fine-tuning of their heating properties. However, the interactions of such IONP additives in material composites are often neglected and can significantly alter the induction heating mechanism. In this work, we systematically vary the IONP interactions in polydimethylsiloxane composite materials by integrating 1.) dispersed IONPs 2.) supraparticles of IONPs (micrometer-assemblies), and 3.) oven-dried hard agglomerated IONPs. Additionally, these three levels of interaction are investigated for three different IONPs types (dodecahedrally and octahedrally shaped, as well as cobalt-doped). In general, dispersed IONPs reveal a broader hysteresis and therefore a faster heating curve. We highlight that not only IONP characteristics (size, morphology, doping), but also excitation field strength and foremost IONP interactions in the composite materials are parameters that are interdependent regarding induction heating and need to be considered as such for optimization in an application-oriented scenario.<br
Created from Fastlane, Scopus look-up
Keywords: Iron oxide nanoparticles; Induction heating; Magnetic interactions; Nanoparticle morphology; Micro-assemblies; Coercive field strength

Investigation of Centrifugal Fractionation with Time-Dependent Process Parameters as a New Approach Contributing to the Direct Recycling of Lithium-Ion Battery Components - Sinn, Tabea; Flegler, Andreas; Wolf, Andreas; Stuebinger, Thomas; Witt, Wolfgang; Nirschl, Herrmann; Gleiß, Marco (Metals, 2020)
Recycling of lithium-ion batteries will become imperative in the future, but comprehensive and sustainable processes for this are still rather lacking. Direct recycling comprising separation of the black mass components as a key step is regarded as the most seminal approach. This paper contributes a novel approach for such separation, that is fractionation in a tubular centrifuge. An aqueous dispersion of cathode materials (lithium iron phosphate, also referred to as LFP, and carbon black) serves as exemplary feed to be fractionated, desirably resulting in a sediment of pure LFP. This paper provides a detailed study of the commonly time-dependent output of the tubular centrifuge and introduces an approach aiming to achieve constant output. Therefore, three different settings are assessed, constantly low, constantly high and an increase in rotational speed over time. Constant settings result in the predictable unsatisfactory time-variant output, whereas rotational speed increase proves to be able to maintain constant centrate properties. With further process development, the concept of fractionation in tubular centrifuges may mature into a promising separation technique for black mass in a direct recycling process chain.<br

Magnetic in situ determination of surface coordination motifs by utilizing the degree of particle agglomeration - Wolf, Andreas; Zink, Andreas; Stiegler, Lisa; Branscheid, Robert; Apeleo Zubiri, Benjamin; Müssig, Stephan; Peukert, Wolfgang; Walter, Johannes; Spiecker, Erdmann; Mandel, Karl (Journal of Colloid and Interface Science, 2023)
Most analytical techniques used to study the surface chemical properties of superparamagnetic iron oxide nanoparticles (SPIONs) are barely suitable for in situ investigations in liquids, where SPIONs are mostly applied for hyperthermia therapy, diagnostic biosensing, magnetic particle imaging or water purification. Magnetic particle spectroscopy (MPS) can resolve changes in magnetic interactions of SPIONs within seconds at ambient conditions. Herein, we show that by adding mono- and divalent cations to citric acid capped SPIONs, the degree of agglomeration can be utilized to study the selectivity of cations towards surface coordination motifs via MPS. A favored chelate agent, like ethylenediaminetetraacetic acid (EDTA) for divalent cations, removes cations from coordination sites on the SPION surface and causes redispersion of agglomerates. The magnetic determination thereof represents what we call a “magnetically indicated complexometric titration”. The relevance of agglomerate sizes for the MPS signal response is studied on a model system of SPIONs and the surfactant cetrimonium bromide (CTAB). Analytical ultracentrifugation (AUC) and cryogenic transmission electron microscopy (cryo-TEM) reveal that large micron-sized agglomerates are required to significantly change the MPS signal response. With this work, a fast and easy-to-use characterization method to determine surface coordination motifs of magnetic nanoparticles in optically dense media is demonstrated.
Keywords: Superparamagnetic iron oxide nanoparticles (SPIONs); Magnetic particle spectroscopy (MPS); Agglomeration; Colloidal surface chemistry; Cation coordination

Magnetic Supraparticles Capable of Recording High‐Temperature Events - Wolf, Andreas; Sauer, Julian; Hurle, Katrin; Müssig, Stephan; Mandel, Karl (Advanced Functional Materials, 2024)
Superparamagnetic iron oxide nanoparticles (SPIONs) are prone to oxidation at elevated temperatures (>300 °C) and lose their magnetizability upon transition from magnetite/maghemite (γ-Fe2O3 / Fe3O4) to hematite (α-Fe2O3). Silica (SiO2) shells can effectively prevent this undesired effect up to ≈1000 °C. Herein, the study shows how to utilize SPIONs with varying SiO2 shell thickness and thus, different oxidation susceptibility, and how to combine them in micrometers sized assemblies – so-called supraparticles (SPs), to create a structurally emerging magnetic temperature recording functionality. The desired oxidation of non or weakly-protected SPIONs within SPs upon temperature events reduces dipole–dipole interactions of well-protected SPIONs in the confined SP entity. The resulting change of magnetic interactions therefore contains information on the thermal history of the SP, which can be spectrally read out via magnetic particle spectroscopy within seconds. Their working range can be tuned from 400 to 1000 °C on two independent structural hierarchy levels, namely the SiO2 shell thickness and the freely selectable ratios of different building blocks in the SP. The application of such SPs as particulate additives for magnetic recording of high-temperature events, especially relevant in metal, alloy, and ceramic processing, representing a yet unexplored and optically-independent option for bulk temperature recording is proposed.<br
Keywords: high-temperature events; magnetic particle spectroscopy; magnetic recorders; smart additives; supraparticles

NanoMOF‐Based Multilevel Anti‐Counterfeiting by a Combination of Visible and Invisible Photoluminescence and Conductivity - Maxeiner, Moritz; Maile, Ruben; Cuvalli, Murat; Wolf, Andreas; Komal, Ayisha; Oestreich, Robert; Janiak, Christoph; Mandel, Karl; Knebel, Alexander; Mueller-Buschbaum, Klaus (Advanced Functional Materials, 2025)
This study presents nanosized metal-organic framwork (nanoMOF)-based multifunctional mixed-matrix-membranes (MMMs) and composite powders as extremely sensitive responder materials for a responder-stimulus based multilevel anti-counterfeiting. The physicochemical properties of nanoMOF-based composites offer a wide operational range as anti-counterfeiting tags. Nine responder materials are presented, constituted of trivalent lanthanide-containing nanoMOFs ([Ln3(bdc)4.5(H2O)3(dmf)2] (nLn-bdc); bdc2−═benzene-1,4-dicarboxylate; Ln═Eu, Tb, Yb) and polystyrene sulfonate, pyrolyzed resorcinol-formaldehyde and polysulfone as matrices. These materials inherit distinct properties, and their combination provides visible and near-infrared light emission and specific conductivity for multiple security level anti-counterfeiting. The additive and interdependent nature of security features in the developed anti-counterfeiting materials ensures that altering one feature will invariably affect others, thereby reinforcing the overall integrity and resilience of the security mechanism. Even the pitch-black composites of nLn-bdc and pyrolyzed resorcinol-formaldehyde show bright light emission to the near-infrared range, when stimulated by UV-light being suitable for black materials. This work also describes a matrix-based active contribution as security feature to an anti-counterfeiting tag, instead of being solely used as a carrier for the security feature-bearing nanoMOFs. The combination of multiple levels of security by different properties marks these multifunctional composites as anti-counterfeiting materials being complicated to copy including a proof-of-principle experimen

Nanoparticle Clustering in Supraparticles to Control Magnetic Long-Range Interactions - Wolf, Andreas; Zhou, Huanhuan; Groppe, Philipp; Stiegler, Lisa; Kämäräinen, Tero; Peukert, Wolfgang; Walter, Johannes; Wintzheimer, Susanne; Mandel, Karl (Particle & Particle Systems Characterization, 2024)
To tailor superparamagnetic iron oxide nanoparticles (SPIONs) to the specific needs of diverse application fields, it is essential to understand not only their intrinsic properties but also their interactions with each other. Theoretical models predicting/explaining the magnetization behavior of macroscopic samples containing millions of SPIONs are intricate due to the complexity of the underlying relaxation mechanisms in alternating fields. This study introduces supraparticles (SPs) as model architectures to empirically investigate magnetic interactions within and between large SPION clusters (>100 nanoparticles (NPs)). For this purpose, NP dispersions containing SPIONs and silica (SiO2)NPs as non-magnetic building blocks are spray-dried to form binary SPs. Selective salt-induced agglomeration of the two building block types before spray-drying is utilized to tailor SP architectures, including control over SPION cluster size, shape, and proximity. Magnetic particle spectroscopy (MPS), operating under ambient conditions, reveals altered magnetization behavior for different cluster structures. Not only the nearest SPION neighbors, but the whole cluster structure up to several micrometers is decisive for the magnetization behavior. This highlights the importance of long-range magnetic interactions. This work presents a versatile approach for designing model architectures to advance empirical interaction studies between SPIONs in macroscopic samples.
Created from Fastlane, Scopus look-up
Keywords: magnetic interactions; magnetic particle spectroscopy; selective agglomeration; spray-drying; superparamagnetic iron oxide nanoparticles; supraparticles

Supraparticles for Sustainability - Wintzheimer, Susanne; Reichstein, Jakob; Groppe, Philipp; Wolf, Andreas; Fett, Bastian; Zhou, Huanhuan; Pujales Paradela, Rosa; Miller, Franziska; Müssig, Stephan; Wenderoth, Sarah; Mandel, Karl (Advanced Functional Materials, 2021)
The indispensable transformation to a (more) sustainable human society on this planet heavily relies on innovative technologies and advanced materials. The merits of nanoparticles (NPs) in this context are demonstrated widely during the last decades. Yet, it is believed that the impact of particle-based nanomaterials to sustainability can be even further enhanced: taking NPs as building blocks enables the creation of more complex entities, so-called supraparticles (SPs). Due to their evolving phenomena coupling, emergence, and colocalization, SPs enable completely new material functionalities. These new functionalities in SPs can be utilized to render six fields, essential to human life as it is conceived, more sustainable. These fields, selected based on an entropy-rate-related definition of sustainability, are as follows: 1) purification technologies and 2) agricultural delivery systems secure humans “fundamental needs.” 3) Energy storage and conversion, as well as 4) catalysis enable the “basic comfort.” 5) Extending materials lifetime and 6) bringing materials back in use ensure sustaining “modern life comfort.” In this review article, a perspective is provided on why and how the properties of SPs, and not simply properties of individual NPs or conventional bulk materials, may grant attractive alternative pathways in these fields.
CRIS-Team Scopus Importer:2021-02-05
Keywords: nanomaterials; nanoparticles; supraparticles; sustainability